Neonatal jaundice causes and management - Althomali, Ruya; Aloqayli, Renad; Alyafi, Basma; Nono, Ahela; Alkhalaf, Suhaib; Aljomailan, Abdulaziz; ALHarbi, Hesham; Alqahtani, Abdulrahman; Alherz, Hawra; Aldebani, Moluk (International Journal Of Community Medicine And Public Health, 2018)
80% of healthy neonates present with some degree of hyperbilirubinemia after birth, however, only 5-10% would require therapy to prevent damage or treat the cause of jaundice. Neonatal jaundice can be classified as physiological and pathological and can have several causes such as breast milk feeding, blood group incompatibility, hemolysis, or genetic defects of enzymes in the bilirubin metabolism pathway. We tried to understand the various types of neonatal jaundice, and also focus on its management. We conducted this review using a comprehensive search of MEDLINE, PubMed and EMBASE from January 2001 to March 2017. The following search terms were used: neonatal jaundice, hyperbilirubinemia, ABO incompatibility, neonatal hemolysis, kernicterus, phototherapy, exchange transfusion. Hyperbilirubinemia and jaundice are common issues encountered neonates and infants. Most cases of neonatal hyperbilirubinemia and jaundice are physiological and benign. However, some severe cases may progress to develop severe and permanent long-term complications. Therefore, early diagnosis and management is essential. Neonatal jaundice can be treated using phototherapy, pharmacological agents, intravenous immunoglobulins and exchange transfusion in severe cases.